Multicenter Comparison of 3D Spinal Measurements Using Surface Topography with Those from Conventional Radiography - Knott, Patrick; Sturm, Peter; Lonner, Baron; Cahill, Patrick; McCarthy, Richard; Kelly, Michael; Lenke, Lawrence; Betz, Randal; Betsch, Marcel (Spine Deformity, 2016)
Introduction In pediatric spinal deformity the gold standard for curve surveillance remains standing full-column radiographs, but repeated exposure to ionizing radiation motivates us to look for nonradiographic solutions. This study tests a modern system of surface topography (ST) to determine whether it is reliable and reproducible. Methods Patients from 6 pediatric spinal deformity clinics were recruited for enrollment. Inclusion criteria were age 8-18; diagnosis of scoliosis measuring ≥10 and <50 degrees or increased kyphosis of ≥45 degrees. Standing radiographs and ST scans (DIERS Formetric, Diers Medical Systems, Chicago, IL) were obtained on all patients and then measured and compared. A single investigator using a validated electronic measurement tool performed all radiographic measurements. Analysis of reproducibility and comparison of ST and radiographs were done. Results A total of 193 patients were enrolled (148 F [77%]). The mean age was 13.25 years (range 8-18). The scoliosis magnitude was as follows: thoracic average 22.7 ± 10 degrees; lumbar average 19.6 ± 9 degrees. The kyphosis magnitude was 54.0 ± 11 degrees. The reproducibility for each ST parameter for 3 repeated scans was strong (interclass correlation = 0.855-0.944). Comparison to radiographic measurements was strong in the thoracic (r = 0.7) and moderate in the lumbar curve (r = 0.5). There was an average difference of 5.8 degrees in the thoracic spine and 8.8 degrees in the lumbar spine between ST Cobb angle estimates and radiographs. Thoracic kyphosis also had a strong correlation (r = 0.8) with radiographs. Conclusions Although the results are intended to measure similar aspects of deformity as the traditional Cobb angle, the measurement is not intended to be an exact estimation. The utility of ST is in the reproducible quantification of deformity after the initial radiograph has been taken. This has the potential to make longitudinal assessment of change in deformity without serial radiographs.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Curve surveillance; Reliability; Reproducibility; Scoliosis; Surface topography